The european emergency number 112 - the questionnaire - Goniewicz, Krzysztof; Goniewicz, Mariusz; Misztal-Okońska, Patrycja; Pawłowski, Witold; Czerski, Robert (Journal of Education, Health and Sport, 2017)
Introduction. The first links in the rescue chain, the first aid and the call for specialist help, often determine the fate of the victim in a state of sudden threat to life. Therefore, the pyramid of rescue success should be built on the foundation of social rescue. Each reduction in the time of starting first aid increases the number of victims who survive the accident. Objective of the work. The aim of the work was to examine the state of knowledge of students about the European emergency number 112 and to compare knowledge about emergency numbers among various academic communities. Material and method. The study was conducted among students of the Medical University of Lublin, the Medical University of Warsaw, Lublin University of Technology, University of Economics, Law and Medical Sciences in Kielce. 610 respondents, including 402 women and 208 men, took part in the study. The research tool was the author's questionnaire, whose design was modeled on the research "Flash Eurobarometer Series 285". The obtained results were subjected to statistical analysis using the STATISTICA 12.5 program. Conclusions. Most of the respondents (92%) identify the 112 number as an emergency number that allows them to connect to emergency services from anywhere in the European Union. A significant number of respondents (47%) identify the 112 number as an emergency number in Poland. One in three respondents will use the 999 number to contact the emergency services as a witness to an emergency in Poland. Non-medical university students more often (63%) will use the 112 emergency number than medical college students (41%). Respondents (98%) confirmed the usefulness of a unified emergency number throughout Europe, but decided that they were not sufficiently informed about 112 as the European emergency number.